Foreskin cutting beliefs and practices and the acceptability of male circumcision for HIV prevention in Papua New Guinea - MacLaren D; Tommbe R; Mafile'O T; Manineng C; Fregonese F; Redman-Maclaren M; Wood M; Browne K; Muller R; Kaldor J; McBride WJ (My University, 2013)
Background: Male circumcision (MC) reduces HIV acquisition and is a key public health intervention in settings with high HIV prevalence, heterosexual transmission and low MC rates. In Papua New Guinea (PNG), where HIV prevalence is 0.8%, there is no medical MC program for HIV prevention. There are however many different foreskin cutting practices across the country's 800 language groups. The major form exposes the glans but does not remove the foreskin. This study aimed to describe and quantify foreskin cutting styles, practices and beliefs. It also aimed to assess the acceptability of MC for HIV prevention in PNG. Methods. Cross-sectional multicentre study, at two university campuses (Madang Province and National Capital District) and at two 'rural development' sites (mining site Enga Province; palm-oil plantation in Oro Province). Structured questionnaires were completed by participants originating from all regions of PNG who were resident at each site for study or work. Results: Questionnaires were completed by 861 men and 519 women. Of men, 47% reported a longitudinal foreskin cut (cut through the dorsal surface to expose the glans but foreskin not removed); 43% reported no foreskin cut; and 10% a circumferential foreskin cut (complete removal). Frequency and type of cut varied significantly by region of origin (p <.001). Most men (72-82%) were cut between the ages of 10 - 20 years. Longitudinal cuts were most often done in a village by a friend, with circumferential cuts most often done in a clinic by a health professional. Most uncut men (71%) and longitudinal cut men (84%) stated they would remove their foreskin if it reduced the risk of HIV infection. More than 95% of uncut men and 97% of longitudinal cut men would prefer the procedure in a clinic or hospital. Most men (90%) and women (74%) stated they would remove the foreskin of their son if it reduced the risk of HIV infection. Conclusion: Although 57% of men reported some form of foreskin cut only 10% reported the complete removal of the foreskin, the procedure on which international HIV prevention strategies are based. The acceptability of MC (complete foreskin removal) is high among men (for themselves and their sons) and women (for their sons). Potential MC services need to be responsive to the diversity of beliefs and practices and consider health system constraints. A concerted research effort to investigate the potential protective effects of longitudinal cuts for HIV acquisition is essential given the scale of longitudinal cuts in PNG. © 2013 MacLaren et al.; licensee BioMed Central Ltd.
Keywords: Male circumcision; Acceptability; Foreskin cutting; Papua New Guinea; HIV; Prevention; Beliefs; Foreskin; cutting practices; Longitudinal Foreskin cut; Circumferential Foreskin cut; 1117 Public Health and Health Services